1998
DOI: 10.1037/0033-295x.105.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the influence of implicitly activated memories on recall and recognition.

Abstract: A model concerning the influence of implicitly activated information on cued recall and recognition is presented. The model assumes that studying a familiar word activates its associates and creates an implicit representation in long-term working memory. Test cues also activate their associates, with memory performance determined by a sampling process that operates on the intersection of information activated by the test cue with information previously activated by the studied word. Successful sampling is enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
265
1
20

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(301 citation statements)
references
References 90 publications
15
265
1
20
Order By: Relevance
“…Thus, nothing in the immediate or recent environment is responsible as far as one can tell but some combination and spreading of activation did in fact produce the phenomenon, i.e., two activations unrelated in both time and content may produce a mental content that is both unexpected and seems contextually irrelevant (cf. Nelson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, nothing in the immediate or recent environment is responsible as far as one can tell but some combination and spreading of activation did in fact produce the phenomenon, i.e., two activations unrelated in both time and content may produce a mental content that is both unexpected and seems contextually irrelevant (cf. Nelson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in semantic priming experiments such indirect activations have been assessed by measuring reaction times (in a lexical decision task) to target words which are semantically related to previously presented primes (e.g., Fischler, 1977;Neely, 1976;. In addition, there are several other lines of research which have shown that automatic activation of related information in response to a target word can exert strong effects on performance in such different tasks as free recall and recognition (Mandler, & Rabinowitz, 1981;Roediger, & McDermott, 1995), cued recall (Nelson et al, 1998), implicit memory tasks (McDermott, 1997), reading and text comprehension (Kintsch, 1988;Sharkey, & Mitchell, 1985). For example, McDermott (1997) showed that associative activation of a non presented prime word in a list of semantically related words was sufficient to produce priming on both conceptual (i.e., word association test) and perceptual implicit memory tests (such as word stem and word fragment completion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McEvoy and Nelson (Chapter 5) review different techniques for studying implicit memory: the methods of savings and of indirect test instructions, and the process dissociation procedure (see also Chapter 20). They then describe their model of cued recall that incorporates both implicit and explicit memory processes (PIER2, which is described in Chapter 5; Nelson et al, 1998), and illustrate it with examples relevant to addictive behaviors. Section II focuses on assessment paradigms and their theoretical basis.…”
Section: General Outline Of the Bookmentioning
confidence: 99%
“…In other words, “the greater the associative‐spreading along the associative connections is (Collins and Loftus 1975; Anderson 1983), the greater is the activation “echo” from associated units back to the target item's unit (Nelson et al. 1998)” (Hofmann et al. 2011, p. 2).…”
Section: Discussionmentioning
confidence: 99%